Association of C-reactive Protein in Preeclampsia - Akter, Jahanara; Begum, Shamsun Nahar; Akter, Pervin; Manjuri, Mamata; Rehana, Zenat; Salma, Umme (Medicine Today, 2024)
Introduction: Preeclampsia is a multisystemic disorder that complicate about 7-10 percent of human pregnancies.Worldwide this syndrome contributes high maternal and perinatal mortality and morbidity. C-reactive protein, a marker of tissue damage and inflammation, is elevated in seurm in overt preeclampsia. It is used as an objective and sensitive index of overall inflammatory activities in the body. Aims and Objectives: To explore the association of C-reactive protein level with the preeclampsia patients. Materials and Methods: The present study was a Case–Control study, conducted in the Department of Obstetrics and Gynaecology in collaboration with the Department of clinical pathology of Sir Salimullah Medical College Hospital, Mitford, Dhaka during the period of January 2013 to December 2013.The study population was pregnant women with preeclampsia and normal term pregnant patients admitted during study period. A total of 66 patients were included in the study. Among them 33 were clinically diagnosed preeclampsia women grouped as Cases and another 33 were age, parity and BMI matched term pregnant women as Controls. Eastmation of serum C-reactive protein was done by Nyco Card Reader-II method (Appendix-11). Statisticians analysis was perform by using SPSS. Results: C-reactive protein concentration (mg/L) was found significantly higher (p<0.001) in case group (17.93±10.5) than control group (7.45±1.80). Creactive protein was _ 6mg/L in 29(87.9%) in case group and 9 (27.3%) in control group and C-reactive protein values showed significant positive correlation with systolic and diastolic blood pressure (p<0.001) in case group. C-reactive protein concentration was found significantly higher (p<0.001) in severe preeclampsia group than mild preeclampsia group. Conclusion: Therefore, it can apparently be concluded from this study that increased maternal serum C-reactive protein level might be a strong risk factor for preeclampsia, although the precise role of C-reactive protein in this regard whether causal or consequential, is yet to be determined. Finding of this study might be helpful for formulating a guideline for management of pregnant women with preeclampsia. Medicine Today 2024, Vol.36 (2): 67-71